KESANTUNAN BERBAHASA DALAM FILM DILAN 1990 - Utami, Resti Riyanda; Tressyalina, Tressyalina (Universitas Negeri Padang, 2019)
ABSTRACT This research is background because politeness involves part of social rules and strategic competencies needed and need to be discussed in the communication process. This research aims to (1) describe politeness strategies in the Dilan 1990 movie; (2) describe the politeness principle of language in the film Dilan 1990; and (3) describe the language context in the Dilan 1990 movie. This type of research is qualitative with descriptive methods. The data of this research are speeches expressed by Dilan’s Mother and Milea which contain politeness strategies, politeness principles, and contexts in the Dilan 1990 movie, analyzing data with the following steps. The first stage, identifying data based on strategy. The second stage, classifies data based on the principle of politeness. The third stage, identifying data based on context. The fourth stage analyzes and discusses research data in accordance with the theory used. The fifth, draws conclusions, namely formulating a repetitive pattern of strategies, principles of politeness, and context. Based on the results of the research it was concluded: (1) the number of data included in the strategy to speak frankly without further ado more than any other speaking strategy; (2) the maxims used in this study are wisdom macism, generosity maxim, praise maxim, and agreement maxim; (3) the speech of Dilan’s Mother and Milea in the Dilan 1990 movie is polite speech. Kata Kunci: Kesantunan Berbahasa , Strategi, Prinsip, Konteks